Early Effects of Natural Disaster (February 6, 2023, Kahramanmaraş Earthquakes) on Fishery Sector and Suggestions for Process Management: The Case of Hatay - Aydın Demirci; Emrah Şimşek; Semih Kale; Sevil Demirci (Acta Natura et Scientia)
The Kahramanmaraş-centered earthquakes and subsequent tremors that occurred in Türkiye on February 6, 2023, caused great destruction in Hatay province. Naturally, the fishing industry has been directly and indirectly affected by these shocks. Like all people in the region, many fishermen had to suspend their fishing activities for life safety reasons. In this study, earthquake effects on fishermen’s shelters, fishing vessels, retail and wholesale fish trade businesses and aquaculture import-export companies in the region were determined. Like all people in the region, many of the fishing parties had to take a break from their activities due to the safety of life. The fishing sector entered the normalization process much faster than other sectors, about a month after the earthquakes. This paper offers suggestions for the sustainable ecosystem concept of the regional fisheries and for obtaining maximum benefit from marine resources. In this process, it is more realistic to support the fishing trade companies (retail, wholesale and export) for the revival of the sector. Because it is thought that the activities of these enterprises will directly reflect on the stakeholders engaged in fishing activities and especially on small-scale fishermen. Considering the martial law decisions taken due to the earthquake within the scope of this support, the inspections should be more effective in order not to cause opportunism.